Kansalaisten kokemukset Suomen ilmastopolitiikan oikeudenmukaisuudesta - Vainio Annukka; Käyhkö Jukka; Loivaranta Tikli; Lundberg Piia; Honkanen Oona (Suomen ilmastopaneeli, 2025)
A survey was conducted in the “Justice in climate change policy” project to discover citizens’ views about
justice in Finland’s climate policy in general, as well as from the perspective of distributional justice,
procedural justice and compensatory justice. The survey was carried out from a regional perspective
and by examining factors affecting vulnerability. The material was collected through an electronic survey
in June 2022. A total of 1,487 people from the following three selected research areas responded to the
survey: Helsinki, Northern Ostrobothnia and Southwest Finland. The material represents the adult
population of the research areas in terms of the type of residential area, gender and age. The responses
to the survey, which included both closed and open-ended questions, were analysed using quantitative,
qualitative and spatial data methods.
Overall, the respondents considered Finland’s current climate policy to be moderately just. Some of the
respondents considered that the climate policy was too ambitious, while some felt that it should be more
ambitious. However, the majority considered it as only seeking more rapid mitigation measures.
Statistically significant differences were found between the different respondent groups. The biggest
differences were found between regions, both in their overall experience of justice, as well as in the
distribution of the impacts of climate policy and participation in it. Differences in perceived justice were
also found regarding the self-assessed economic situation and political orientation. Respondents
considering climate policy most just were characterised by a high level of education, a left-leaning
political orientation and living in cities.
Regarding the justice of climate policy, the majority of the respondents considered it merely to reduce
the economic and regional inequality caused by mitigation measures. The experience of injustice was
most common for statements referring to increased household costs as a result of mitigation measures.
On the other hand, a minority of the respondents considered it unjust that countries that polluted the
most would bear the main responsibility for the costs of mitigating climate emissions, or that Finland
would reduce its emissions regardless of the actions of other countries. A majority of the respondents
also felt that the special needs of different groups and silent parties (such as animals, nature or future
generations) should be taken into account. Contrary to the dimension of distributional and recognitive
justice, the responses assessing the justice of the procedures were more divided: at most, only about
half the respondents agreed at least somewhat with the statements concerning the procedures, and
slightly less than one third or even more than half disagreed with the statements, depending on the
statement. The differences between the responses concerning the various dimensions are probably due
to the fact that the statements of the first two dimensions of justice were related to what Finland’s climate
policy should be like, while the statements measuring the procedures described what Finland’s climate
policy is currently like. The results show that the majority of citizens agree with the principles of justice
in climate policy, but are divided in terms of views about how justice is realised in Finland’s climate policy.
Living in a sparsely populated area seems a factor that increases the experiences of vulnerability most
in view of distributional justice, especially regarding experiences of narrower mobility opportunities. In
turn, educational background was connected with perceived opportunities to participate: the most highly
educated felt their opportunities to participate were better compared with other respondents. The
participation of Finns in climate policy is poor: almost 40 per cent had never participated in it in any way.
The availability of information on participation opportunities was considered rather poor, and participation
was not perceived to have much impact. Highly educated respondents felt that their opportunities to
participate were better compared with other respondents. Helsinki’s residents felt they had been more
actively involved in climate policy compared with other respondents.
According to the survey, the respondents’ general knowledge of climate policy was on average poor,
and the actions or concepts related to climate policy were not well known. There were regional
differences in knowledge: the knowledge of those living in Helsinki was better than that of others. A  connection was found between climate policy knowledge and the experience of justice: those who knew
more about climate policy felt climate policy was more just.
Despite attempts to do so, the survey did not reach enough linguistic minorities. The planning of climate
policy should also consider ways of making the voice of those groups that are more difficult to reach
heard.